2022
DOI: 10.1038/s41598-022-20293-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rhizosphere bacterial communities of tobacco resistant and non-resistant to bacterial wilt in different regions

Abstract: Tobacco bacterial wilt has seriously affected tobacco production. Ethyl methanesulfonate (EMS) induced tobacco bacterial wilt resistant mutants are important for the control of tobacco bacterial wilt. High-throughput sequencing technology was used to study the rhizosphere bacterial community assemblages of bacterial wilt resistant mutant tobacco rhizosphere soil (namely KS), bacterial wilt susceptible tobacco rhizosphere soil (namely GS) and bulk soil (namely BS) in Xuancheng, Huanxi, Yibin and Luzhou. Alpha a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…The results indicated that the diseased soils in Youxian and Lichuan may have a significant effect on bacterial diversity. Taken together, the field site location had a large effect in determining microbial community diversity in the present study, which is similar to previous studies that illustrated the importance of spatial influences [47,54,55].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicated that the diseased soils in Youxian and Lichuan may have a significant effect on bacterial diversity. Taken together, the field site location had a large effect in determining microbial community diversity in the present study, which is similar to previous studies that illustrated the importance of spatial influences [47,54,55].…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that the soil pH values of Lichuan and Jianshi were lower than those of Licang and Youxian, while the corresponding bacterial Chao1 indices of healthy and diseased soils in the two regions were, overall, at low levels among the four regions. Thus, soil pH may be one of the factors affecting bacterial diversity, which is in line with previous studies [ 47 , 48 ]. A high calcium concentration can reduce the rate of maturation of P. brassicae in root hairs and clubroot severity in Brassica crops [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 90%
“…TBW is a bacterial disease, and TBS is a fungal disease, which usually results in severe losses of yield and quality of tobacco, so that TBW and TBS can be excellent model for biocontrol research. The first task is to find effectively broad-spectrum microorganisms ( Zheng et al., 2021 ; Shi et al., 2022 ). In this study, we studied the response of rhizosphere soil microbial communities to these two plant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used methods mainly include chemical pesticides and transgenic approaches, which cannot eliminate TMV load in infected tobacco plants and whose efficacy is still limited in the field. Microbes (e.g., Streptomyces , Pseudomonas , and Bacillus ) have been considered potential alternatives for chemical pesticides to inhibit plant pathogens, including fungal, bacterial, and viral pathogens ( Kim et al, 2022 ; Ren et al, 2022 ; Shi et al, 2022 ). Pseudomonas fluorescens could inhibit the activity of Cucumber mosaic virus , Tomato mottle virus , and Tobacco necrosis virus ( Maurhofer et al, 1998 ; Murphy et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%